2017
DOI: 10.1093/humrep/dex283
|View full text |Cite
|
Sign up to set email alerts
|

Preconception urinary phthalate concentrations and sperm DNA methylation profiles among men undergoing IVF treatment: a cross-sectional study

Abstract: This work was supported by grant K22-ES023085 from the National Institute of Environmental Health Sciences. The authors declare no competing interests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(55 citation statements)
references
References 53 publications
3
52
0
Order By: Relevance
“…Twelve of the fifteen phthalate metabolites were measured above the LOD in more than 90% of samples (MEOHP, MEHHP, MECPP, MBzP, MBP, MHBP, MHiBP, MMP, MCOP, MEP, MCPP, and MCNP). Urinary phthalate concentrations in the current study are in line with those reported previously by our group (Wu et al, 2017b, 2017c) and others (CDC, 2010; Dodge et al, 2015). Lower urinary concentrations were observed for the two metabolites of DINCH, a phthalate alternative, with 38% > LOD for MCOCH and 63.1% > LOD for MHINCH.…”
Section: Resultssupporting
confidence: 93%
“…Twelve of the fifteen phthalate metabolites were measured above the LOD in more than 90% of samples (MEOHP, MEHHP, MECPP, MBzP, MBP, MHBP, MHiBP, MMP, MCOP, MEP, MCPP, and MCNP). Urinary phthalate concentrations in the current study are in line with those reported previously by our group (Wu et al, 2017b, 2017c) and others (CDC, 2010; Dodge et al, 2015). Lower urinary concentrations were observed for the two metabolites of DINCH, a phthalate alternative, with 38% > LOD for MCOCH and 63.1% > LOD for MHINCH.…”
Section: Resultssupporting
confidence: 93%
“…Collectively, our findings demonstrate that two common endocrine disruptors are capable of causing aberrant DNA methylation of CpG islands in sperm and the brain and that a few of these sites are faithfully transmitted for multiple generations. EDC exposure has been shown to be associated with altered DNA methylation in humans for dioxins [78], flame retardants like organophosphates [44] and polybrominated diphenyl ethers [79], phthalates [80], and PCBs [81]. To our knowledge, a similar study has not been performed for VIN in humans.…”
Section: Discussionmentioning
confidence: 84%
“…Mechanistically, it is thought that germ cells and preimplantation embryos are most susceptible to endogenous and exogenous environmental factors because the epigenome in these cells undergoes dramatic reprogramming [92,93]. While causal links have not been established between individuals' exposures, epigenetic alterations in germ cells and cancer risk in their children, factors such as dietary folate, alcohol, obesity, smoking, endocrine disrupters, and phthalates have been shown to alter epigenetic marks in germ cells [94][95][96][97][98][99][100]. Animal studies have shown some provocative findings.…”
Section: Towards a Better Understanding Of How Exposures Affect Breasmentioning
confidence: 99%